(untitled) (Castilla. Estudios de Literatura, 2013)
This study analyses the poems by Quevedo against Góngora in the light of the controversy surrounding Soledades and the poetic dispute between don Luis and Lope de Vega. In those verses don Francisco praised Lope´s talent, reproached Góngora for his satires on Lope, expressed the same criticisms of the cultist style than Lope, Jáuregui and other polemicists, and attacked the Cordovan poet in the most explicit and aggressive way.